Feeling hopeful: development and validation of the trait emotion hope scale - Feldman, David B.; Jazaieri, Hooria (Frontiers in Psychology, 2024)
While prominent measures of hope are largely cognitive in nature, many scholars and laypeople view hope primarily as an emotion. Although Snyder's (2002) Elaborated Hope Theory attempts to theoretically balance these two perspectives, no measure yet exists of hope as an emotional process, only as a cognitive process. Overlooking the emotional features of hope limits our ability to more fully and precisely understand this construct. As such, across three studies (N = 2,900), we develop and validate the Trait Emotion Hope Scale (TEHS). In Study 1, we report on item development and piloting of the TEHS, examining internal consistency as well as convergent and discriminant validity. Study 2 includes an exploratory factor analysis (EFA) and further examines internal consistency and construct validity. Finally, in Study 3 we report a confirmatory factor analysis (CFA) to cross-validate the factor structure identified in Study 2 in a large, international sample. Importantly, we find that the TEHS accounts for significant unique variance beyond cognitive hope, indicating that the two constructs are distinct and not redundant. Taken together, these three studies demonstrate that the TEHS is psychometrically sound and provides a valid measure for those interested in examining hope as an emotion in their research.